FRAKSINASI DAN BIOAVAILABILITAS LOGAM BERAT Fe DAN Mn PADA SEDIMEN DI PELABUHAN BENOA - Sahara, Emmy; Widihati, Ida Ayu Gede; Darma Putra, I Gede (Jurnal Kimia (Journal of Chemistry); Vol. 9, no. 1 Januari 2015, 2015)
A research on metal fractionation and bioavailability of Fe and Mn in sediments collected from the area of Benoa Bay at Bali has been carried out. The purpose of this study was to determine the fraction of Fe and Mn in the sediments and their bioavailabilities. Fractionations were achieved by the Sequential Extraction methods during which various solutions were employed. Measurement of the concentration of both metals was done by using Atomic Absorption Spectrofotometer with a calibration curve method. The concentrations of total Fe and Mn in the sediment obtained were of 668.2948 mg/kg and 321.5761 mg/kg, respectively. The results of Fe and Mn fractionations in sediments were as follow: the fraction of freely, leachable and exchangeable (EFLE) were of 27.74% and 24.31%, the fractions of Fe/Mn-oxides were of 23.55% and 19.99%, organic and sulfide fraction were of 25.14% and 26.11% while the resistant fraction were of 23,57% and 29,59%, respectively. It Therefore, the results showed that the bioavailable and the resistant fractions for Fe in the sediment were of 76.43% and 23,57%, respectively while for Mn were of 70.41% and 29,59%, respectively
Keywords: fractination, bioavailability, Fe, Mn, sediment, Benoa Bay